Senior High School Students’ Motivation to Enroll in English Language Schools - Arief, Rahmi; Korompot, Chairil Anwar; Sakkir, Geminastiti (State University of Makassar, 2024)
This research aims to find out what students' motivations are when enroll an English Language Schools. This research used a qualitative research method with a qualitative descriptive design involving 7 grade 3 students at SMA Negeri 3 Makassar. Data collection techniques include observation, interviews and documentation. The result of this research reveals that several students’ motivations when enrolling for an English Language schools experienced intrinsic and extrinsic motivation. But the most dominant motivation is extrinsic motivation.Keywords: Motivation, Intrinsic and Extrinsic Motivation, English Language Schools.